(untitled) (Jurnal Pustaka, 2026)
Religious sociopathology is increasingly becoming a complex and profound problem in educational settings. This journal examines the main challenges that education faces in dealing with religious sociopathology and suggests solutions that can help overcome these problems. The research used document review methods and interviews with education experts and religious leaders to develop effective solutions. The results show that inclusive education, interfaith dialog and a deep understanding of religious values can be effective solutions to overcome religious social pathology in the educational environment. This research aims to support efforts to make education a tool to promote peace, tolerance and respect for diversity in society